Junie b. jones collection, books 17-20 eaudiobook - Park, Barbara (Junie B. Jones,, 2007)
Junie B. is back, and she's headed for the first grade with four more fun-filled stories in one audiobook collection. This collection includes: Junie B. Jones Is a Graduation Girl #17 Junie B., First Grader (at last!) #18 Junie B., First Grader: Boss of Lunch #19 Junie B., First Grader: Toothless Wonder #20